The Relation Between Platelet Reactivity and Coronary Angiographic Findings in Young Female Survivors of Acute Myocardial Infarction - Kutti, Jack; Wadenvik, Hans; Johansson, Saga; Vilén, Lars; Vedin, Anders; Wilhelmsson, Claes (Thrombosis and Haemostasis, 1986)
In 31 women who had survived their first acute myocardial infarction (MI) studies of platelet reactivity were related to coronary angiographic findings. The results were compared to those obtained from 38 age-matched control women. According to the cardioangiographic findings the group of MI was subdivided into: 9 patients with 1-vessel disease (VD), 10 patients with 2-VD, and 5 patients with 3-VD; 7 subjects did not reveal significant coronary stenosis. When each of these 4 subgroups of MI-patients were compared with the control material significant difference with respect to PF4 was found only for subjects with 1-VD (20.0 ± 4.8 vs. 10.3 ± 0.6 ng/ml). As regards BTG the difference was significant for 1-VD and 2-VD patients (69 ± 12 and 59 ± 3, respectively vs. 40 ± 2 ng/ml). The cumulative frequency for secondary aggregation differed only as regards 1-VD patients (78 vs 40%).
Keywords: Coronary artery disease; Beta-thromboglobulin; Platelet factor 4; Platelet aggregation